INFLUENCE OF CELEBRITY ENDORSER AND BRAND IMAGE ON PURCHASE DECISION OF ERIGO PRODUCTS: (Study on Erigo consumers in Medan City) - Altair Nikolas Tarigan; Posma Lumban Raja (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
This research aims to determine how the effect of celebrity endorser on purchasing decisions, how the effect of brand image on purchasing decisions, as well as the effect of Celebrity endorser and brand image on the purchasing decisions of Erigo consumers in Medan City. This research uses a quantitative type of research with an associative approach. Sampling using purposive sampling technique using 100 respondents as a research sample. Primary Data in this study were obtained from distributing questionnaires through google form, and secondary data were obtained through library studies. The analysis method used is validity test, classical assumption test, reliability test, multiple linear regression analysis and hypothesis test. The results showed that Celebrity endorser and brand images have a positive and significant effect on purchasing decisions. Based on the results of the determination test, the results were obtained that the value of the correlation coefficient (R2) was 0.890 (89%), where the value of this correlation coefficient showed that the relationship between celebrity endorsers and brand image to purchasing decisions was quite strong. The value of R Square or the value of the coefficient of determination shows that the purchase decision variable of 79.1% can be explained by the Celebrity endorser and brand image variables, while the remaining 20.9% is influenced by other variables beyond this study.